1997
DOI: 10.1002/(sici)1096-9071(199711)53:3<189::aid-jmv2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for cytomegalovirus infection in organ transplant recipients: Analysis of pp65 antigen, DNA and late mRNA in peripheral blood leukocytes

Abstract: The use of sensitive and specific methods for rapid and reliable diagnosis is required due to the considerable impact of human cytomegalovirus (HCMV) in organ transplant recipients. For this purpose the demonstration of the presence of viral antigens in peripheral blood leukocytes (PMNLs) and of viral nucleic acids in the same cells or in sera would seem to be of valid support. The present study was designed to test pp65 antigen, HCMV DNA and HCMV late mRNA in order to provide clinical information for the mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…However, some studies have demonstrated that a patient with a small number of pp65-positive cells may still develop CMV disease, while some patients with larger numbers of positive cells resolve their infection spontaneously, without antiviral therapy (106). These divergent observations and the lack of a defined standardized threshold are likely due to the various risks among SOT recipients (highest among lung recipients and lower among kidney recipients), their preexisting CMV-specific immunity (highest among CMV Dϩ/RϪ patients compared to others), and the severity of pharmacologic immunosuppression (highest with lymphocyte-depleting drugs) (83,84,88,(106)(107)(108)(109).…”
Section: Antigen Testingmentioning
confidence: 99%
“…However, some studies have demonstrated that a patient with a small number of pp65-positive cells may still develop CMV disease, while some patients with larger numbers of positive cells resolve their infection spontaneously, without antiviral therapy (106). These divergent observations and the lack of a defined standardized threshold are likely due to the various risks among SOT recipients (highest among lung recipients and lower among kidney recipients), their preexisting CMV-specific immunity (highest among CMV Dϩ/RϪ patients compared to others), and the severity of pharmacologic immunosuppression (highest with lymphocyte-depleting drugs) (83,84,88,(106)(107)(108)(109).…”
Section: Antigen Testingmentioning
confidence: 99%
“…The presence of a small number of antigen-positive cells following solid-organ transplantation generally indicates asymptomatic infection, whereas a large number implies an increased likelihood of CMV disease; the exact cutoffs for this assay, however, remain to be defined and may vary among different types of transplant recipients and among individual assays (142,266,311,323,466,505). While antigenemia is highly sensitive and specific for the diagnosis of CMV infec- tion, both the specificity and positive predictive value of the test for the diagnosis of CMV disease are less impressive; that is, patients with asymptomatic infection are frequently antigenemia positive (313,505).…”
Section: Antigenemia Assaymentioning
confidence: 99%
“…Although PCR is extremely sensitive and specific in detecting the presence of CMV DNA, there is the concern that a positive signal resulting from the presence of very few DNA copies may not differentiate between replicating and latent viruses (91,142,157,507). On the other hand, negative CMV detection by PCR strongly advocates against CMV infection (33,278,347,448).…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…This time course is in concordance with the onset of viral DNA replication [16]. RT-PCR assays of different target sequences from IE to late stages of transcription have been developed for clinical diagnosis of hCMV disease [1,4,5,13]. However, with the exception of IE transcripts all mRNAs tested are unspliced (pp150, pp65, pp67).…”
Section: Discussionmentioning
confidence: 84%
“…Immediately early (IE) gene transcription is independent of protein synthesis, early transcription (E) is independent of viral DNA synthesis, and late gene transcription corresponds to viral DNA replication. Reactivation of hCMV from the latent state is associated with the transcription of late genes encoding phosphoproteins (pp150), glycoproteins (gB), proteins of unknown functions and mRNAs with unknown translation products [2,4]. As the majority of hCMV genes are unspliced, discrimination of viral DNA and mRNA using polymerase-chain-reaction (PCR) primers spanning exon/exon boundaries is complicated.…”
Section: Introductionmentioning
confidence: 99%